2017
DOI: 10.5296/emsd.v6i1.11108
|View full text |Cite
|
Sign up to set email alerts
|

A Brief Answer: Why is China's Aquaculture Industry so Successful?

Abstract: As wild capture fisheries continue to be exhausted worldwide, aquaculture is being looked as the sustainable solution to meet the global fisheries demand. China is one of the most successful countries in the world when it comes to aquaculture. They produce more fish than they catch, simultaneously providing for their own country and the rest of the world. By contrast, the United States imports over 90% of its fisheries; its aquaculture industry meeting only 5% of the country"s total demand of fish. While the U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Along with the fast growth of marine pond aquaculture, and with the development of society, science and technology, the marine pond aquaculture model has been progressively improved and innovated in China, in response to environmental and social issues, regulations and the implementation of best management practices (Farquhar et al . 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Along with the fast growth of marine pond aquaculture, and with the development of society, science and technology, the marine pond aquaculture model has been progressively improved and innovated in China, in response to environmental and social issues, regulations and the implementation of best management practices (Farquhar et al . 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown the US regulatory environment to have inhibited industry development (Abate et al, 2016(Abate et al, , 2018Farquhar et al, 2017;Kite-Powell et al, 2013;Knapp & Rubino, 2016). Sluggish and often negative aquaculture growth in Japan, the European Union, and the United States was found to result from stringent regulatory environments (Abate et al, 2016).…”
mentioning
confidence: 99%
“…13610, 2012). The rapid development and evolution of commercially viable aquaculture technologies has occurred during this period of increasing regulatory burdens in the USA and the European Union (EU), likely contributing to the much slower growth of aquaculture in the USA and the EU (Thunberg et al 1994; Engle and Stone 2013; Kite‐Powell et al 2013; Abate et al 2016; Farquhar et al 2017; Osmundsen et al 2017). Thus, understanding which regulations are most costly and most constraining to both well‐established sectors of U.S. aquaculture and to newer, emerging sectors, is an essential step to develop more streamlined and cost‐effective approaches to governance.…”
Section: Introductionmentioning
confidence: 99%